PENGARUH SISTEM KEUANGAN DESA TERHADAP KINERJA PEMERINTAH DESA DENGAN GOOD GOVERNANCE SEBAGAI VARIABEL INTERVENING DI KABUPATEN KULON PROGO (Studi Kasus di Kecamatan Panjatan) - Wihastinelahi Wihastinelahi; Teguh Erawati (Journal Competency of Business, 2020)
This research was conducted to find out the role of village financial system (Siskeudes) on the performance of village administration with good governance as an intervening variable in Kulon Progo Regency. This research employed quantitative research approach. The data used were primary data. The informants used were village Kaur and Kasi, the village secretaries, the village financial system operators (Siskeudes). The result showed that: (1) village financial system (Siskeudes) influences on the good governance; (2) good governance influences on the performance of the village administration; (3) village financial system (Siskeudes) no effect to performance of village administration; (4) village financial system (Siskeudes) on the performance of village administration with good governance an an intervening variable.